Child Farm Labor : The Wealth Paradox - Bhalotra, Sonia; Heady, Christopher (Washington, DC: World Bank, 2014)
This article is motivated by the remarkable observation that children of land-rich households are often more likely to be in work than the children of land-poor households. The vast majority of working children in developing economies are in agricultural work, predominantly on farms operated by their families. Land is the most important store of wealth in agrarian societies, and it is typically distributed very unequally. These facts challenge the common presumption that child labor emerges from the poorest households. This article suggests that this apparent paradox can be explained by failures of the markets for labor and land. Credit market failure will tend to weaken the force of this paradox. These effects are modeled and estimates obtained using survey data from rural Pakistan and Ghana. The main result is that the wealth paradox persists for girls in both countries, whereas for boys it disappears after conditioning on other covariates.